La responsabilidad social del docente para la construcción de la paz - Galindo Mahecha, Magda LeoniIde; Ruiz Ramírez, Milton Yohany (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents a reflective process on the importance of the teacher to develop citizenship skills from the pedagogical level with the chair of peace. The experiences of the tutor and the student were retaken during the training process and development of the subjects of the General area: Guidelines and Educational Didactics in Ethics, Values and Religion, Humanistic Partner I and II and Ethics and Policy of the Degree in Basic Education with emphasis in Mathematics, Humanities and Spanish Language, from the Regional Center for Distance Studies of Bogotá. It was complemented with articles, documents and related legislation; the theo- retical contributions were articulated with the experiences in the classroom and the teaching experiences. The conclusions call for the university professors of the Bachelor’s Degree and the Graduates in formation to develop the chair of peace, in practical form from the classrooms; through his teaching practice.